Coherent control of D2/H2 dissociative ionization by a mid-infrared two-color laser field. (16th December 2015) - Wanie, Vincent; Ibrahim, Heide; Beaulieu, Samuel; Thiré, Nicolas; Schmidt, Bruno E; Deng, Yunpei; Alnaser, Ali S; Litvinyuk, Igor V; Tong, Xiao-Min; Légaré, François
Abstract: Steering the electrons during an ultrafast photo-induced process in a molecule influences the chemical behavior of the system, opening the door to the control of photochemical reactions and photobiological processes. Electrons can be efficiently localized using a strong laser field with a well-designed temporal shape of the electric component. Consequently, many experiments have been performed with laser sources in the near-infrared region (800 nm) in the interest of studying and enhancing the electron localization. However, due to its limited accessibility, the mid-infrared (MIR) range has barely been investigated, although it allows to efficiently control small molecules and even more complex systems. To push further the manipulation of basic chemical mechanisms, we used a MIR two-color (1800 and 900 nm) laser field to ionize H2 and D2 molecules and to steer the remaining electron during the photo-induced dissociation. The study of this prototype reaction led to the simultaneous control of four fragmentation channels. The results are well reproduced by a theoretical model solving the time-dependent Schrödinger equation for the molecular ion, identifying the involved dissociation mechanisms. By varying the relative phase between the two colors, asymmetries (i.e., electron localization selectivity) of up to 65% were obtained, corresponding to enhanced or equivalent levels of control compared to previous experiments. Experimentally easier to implement, the use of a two-color laser field leads to a better electron localization than carrier-envelope phase stabilized pulses and applying the technique in the MIR range reveals more dissociation channels than at 800 nm.